IMPLEMENTASI PASAL 8 AYAT (2) UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN ATAS KETIADAAN INFORMASI DALAM PRAKTIK JUAL BELI PAKAIAN BEKAS DI KOTA MALANG (Studi di Kota Malang) - Lalu Muhammad Nuki Pratama Hadi (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Lalu Muhammad Nuki Pratama Hadi, Yuliati, Shinta Puspitasari Fakultas Hukum Universitas Brawijaya e-mail: lalumuhammadnuki11@gmail.comÂ  ABSTRAK Skripsi ini mengangkat permasalahan Implementasi Pasal 8 Ayat (2) Undang- Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen Atas Ketidaan Informasi Dalam Praktik Jual Beli Pakaian Bekas Di Kota Malang. Pilihan tema tersebut dilatarbelakangi oleh adanya larangan pasal tersebut yang juga menyebutkan bahwa pelaku usaha dilarang memperdagangkan barang yang rusak, cacat atau bekas dan tercemar tanpa memberikan informasi secara lengkap dan benar atas barang dimaksud, tetapi dalam kenyataanya masih banyak pelaku usaha memperdagangkan pakaian impor bekas yang tercemar tanpa informasi yang benar. Berdasarkan hal tersebut, karya tulis ini mengagkat rumusan masalah : (1) Bagaimana implementasi pasal 8 ayat 2 undang-undang Nomor 8 Tahun 1999 tentang perlindungan konsumen mengenai larangan perdagangan barang yang rusak, cacat, atau bekas dan tercemar tanpa memberikan informasi secara lengkap dan benar terhadap pelaku usaha di kota Malang? (2) Bagaimana bentuk pertanggungjawaban pelaku usaha kepada konsumen terhadap praktik perdagangan pakaian impor dalam mewujudkan perlindungan kepada konsumen?. Kemudian penulis meggunakan metode yuridis empiris. Skripsi ini didasarkan pada teori Implementasi menurut George.C.Edward III (1980), dan dasar hukum Pasal 7 huruf (b) , 8 ayat (2) Undang- Undang Nomor 8 Tahun 1999 tentang Perlindungan konsumen, Peraturan Menteri Perdagangan Republik Indonesia Nomor 12 Tahun 2020 tentang Barang Dilarang Impor. Hasil yang di peroleh mengindikasi bahwa Implementasi Pasal 8 Ayat (2) Undang- Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen Atas Ketiadaan Informasi Dalam Praktik Jual Beli Pakaian Bekas Di Kota Malang masih belum terlaksana dengan baik. Kata Kunci : Implementasi, Perlindungan Konsumen, Pakaian Impor BekasÂ ABSTRACT This research studies Article 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection over unjust information in used cloth sale in Malang city. This topic departs from the article proscribing any sale of damaged, flawed, used, or polluted clothes without giving information on the quality of the sold items to the buyers, contrary to the number of the sellers involved in the trading not providing the intended information. Thus, from this issue, this research investigates: (1) how are articles 8 and 2 of Law Number 8 of 1999 concerning Consumer Protection implemented in the case studied? (2) what responsibility can the business people demonstrate in the case of imported item clothes regarding the protection given to buyers? This research employed empirical-juridical methods based on the theory of implementation introduced by George C. Edward III (1980) and the legal basis of Article 7 letter (b), 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection, the Regulation of the Minister of Trade of the Republic of Indonesia Number 12 of 2020 concerning Proscribed Imported Goods. The research result indicates that Article 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection over the absence of the information in sale and purchase practices of used clothes has not been appropriately implemented in Malang. Keywords: implementation, consumer protection, imported used clothesABSTRACT This research studies Article 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection over unjust information in used cloth sale in Malang city. This topic departs from the article proscribing any sale of damaged, flawed, used, or polluted clothes without giving information on the quality of the sold items to the buyers, contrary to the number of the sellers involved in the trading not providing the intended information. Thus, from this issue, this research investigates: (1) how are articles 8 and 2 of Law Number 8 of 1999 concerning Consumer Protection implemented in the case studied? (2) what responsibility can the business people demonstrate in the case of imported item clothes regarding the protection given to buyers? This research employed empirical-juridical methods based on the theory of implementation introduced by George C. Edward III (1980) and the legal basis of Article 7 letter (b), 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection, the Regulation of the Minister of Trade of the Republic of Indonesia Number 12 of 2020 concerning Proscribed Imported Goods. The research result indicates that Article 8 Paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection over the absence of the information in sale and purchase practices of used clothes has not been appropriately implemented in Malang. Keywords: implementation, consumer protection, imported used clothes